2013
DOI: 10.3329/updcj.v2i2.15483
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Practices in the Outpatient Department in a Tertiary Care Teaching Hospital in Bangladesh

Abstract: A cross-sectional descriptive study was carried out among individuals attending the Out Patient Department (OPD) of Medicine, Paediatrics, Dermatology & Venerology, ENT, Orthopaedics and Gynaecology & Obstetrics from December 2011 to March 2012 in East-West Medical College Hospital, Dhaka, Bangladesh, to see the patterns of prescriptions using World Health Organization (WHO) core prescribing indicators and some additional indices. A total of 300 prescriptions were collected and analyzed by the 3rd year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…The results of the present study revealed that the average number of drugs prescribed per encounter was 3.3 which were not within the recommended range of WHO guideline. Similar prescribing trends were reported from earlier studies in Bangladesh and several other developing countries [9,10,17]. However, practice of prescribing drugs within the WHO recommended range (≤3) was observed in Zimbabwe, Jordan, Brazil, India and Nepal [18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The results of the present study revealed that the average number of drugs prescribed per encounter was 3.3 which were not within the recommended range of WHO guideline. Similar prescribing trends were reported from earlier studies in Bangladesh and several other developing countries [9,10,17]. However, practice of prescribing drugs within the WHO recommended range (≤3) was observed in Zimbabwe, Jordan, Brazil, India and Nepal [18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 76%
“…About 45.6% of drugs in this study were prescribed by generic name which was far less than WHO recommended guideline of 100%. A previous study conducted at a tertiary care hospital of Bangladesh reported the rate of prescription of drugs by generic name around 50%, while another study at a Government referral hospital in northern Bangladesh found no prescription by generic name [9,10], The rate of prescribing drugs in generic name ranges from 27% to 61% in other developing countries of Asia and Africa [10,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result was similar with the study result of Bangladesh (3.22) and Nigeria (3.3). 8,9 The trend of polypharmacy may be due to the patient's expectations and demand of quick relief, the incorrect diagnosis and the influence of the lucrative promotional programs of the drug companies. 4 Polypharmacy is known to cause unnecessary adverse reactions, drug interactions, unnecessary drug expenses and complications.…”
Section: Discussionmentioning
confidence: 99%